한국판 소셜미디어 사용 메타인지 척도 번안 및 타당화 - 강찬휘(Chan-Hwi Kang); 전민탁(Min-Tak Jeon); 장성호(Sungho Jang); 신정미(Jeong-Mi Shin); 신성만(Sung-Man Shin) (한국콘텐츠학회 논문지, 24(4), 2024)
본 연구는 소셜미디어 사용 메타인지 척도(Meta-cognition about Social Media Use Scale)를 한국어로 번안 및 타당화하였다. 이를 위해 원저자의 동의를 받은 후 원척도 12문항을 번안 및 역번안하여 전문가 평정을 받아 번안본 문항을 확정하였다. 이후 연구참여에 동의한 국내 성인 404명에게 설문조사를 실시하고, 그 중 불성실한 응답을 제외한 367명(남자 156명, 여자 211)의 자료를 분석에 활용하였다. 탐색적 요인분석과 확인적 요인분석을 진행한 결과, 모든 문항의 적합도가 양호해 원척도와 동일하게 부정적 메타인지, 긍정적 메타인지의 두 가지 하위요인으로 구성됨을 확인하였다. 또한, SNS 중독경향성 척도와 스마트폰 중독 자가진단 척도, 한국판 역학연구센터 우울 척도, 단축형 자기통제 척도와의 상관관계를 분석하여, 한국판 소셜미디어 사용에 관한 메타인지 척도의 공인 타당도를 확인하였다. 끝으로 척도의 신뢰도를 검증하여 본 척도가 신뢰롭고 타당한 척도임을 확인하였다. 이러한 결과를 바탕으로 본 연구의 의의 및 제한점, 향후 연구를 위한 제언을 논의하였다. This study aimed to translate and validate the Meta-cognition about Social Media Use Scale in Korean(MSMUS-K). For this purpose, the 12 items of the original scale were translated and reverse-translated after obtaining consent from the original author, and the final items were finalized through expert judgment. A survey was conducted with 404 consenting adult participants in Korea, and data from 367 individuals(156 males, 211 females), excluding unreliable responses, were analyzed. Exploratory and confirmatory factor analyses were conducted and the results indicate that all items had good fit, and the scale consisted of two subfactors as the original scale, negative metacognition and positive metacognition. To assess the construct validity, correlations were analyzed between MSMUS-K and the SNS Addiction Proneness Scale, the Smartphone Addiction Proneness Scale for Adults, the Korean version of the Center for Epidemiological Studies-Depression Scale, and the Brief Self Control Scale. MSMUS-K showed significant correlations with all these scales. Finally, the internal consistency reliability of MSMUS-K was adequate. These results indicate that MSMUS-K is reliable and valid scale. Based on these results, the study discussed the significance and limitations of the research, and suggestions for future research. KCI Citation Count: 0